ANÁLISE PRELIMINAR DA ATIVIDADE DE TUTORIA NOS CURSOS DE ESPECIALIZAÇÃO EM GESTÃO PUBLICA E GESTÃO PÚBLICA MUNICIPAL DA UAB-UNIFESP: Percepção de Tutores e Alunos - Candia Hollnagel, Heloisa; de Breláz, Gabriela; Ikeda, Ricardo Hirata; Pereira Bueno, Ricardo Luis (Perspectivas Contemporâneas, 2017)
O presente artigo trata-se de um estudo de caso referente ao Programa Nacional de Formação em Administração Pública da Universidade Aberta do Brasil considerando os cursos de pós-graduação Lato sensu em Gestão Pública (GP) e Gestão Pública Municipal (GPM) oferecidos pelo Campus Osasco da Universidade Federal de São Paulo a partir de relatórios da equipe e uso de formulários eletrônicos na plataforma Google docs para alunos e tutores no módulo básico no primeiro ano de oferta em 2014, pois, o conteúdo e os docentes eram os mesmos nessa etapa de formação da especialização. Os resultados mostram que o papel de tutor ainda não está consolidado, apesar da avaliação positiva dos atores envolvidos. Os resultados deste trabalho abrem novas perspectivas de estudo da atividade de tutoria nos cursos de especialização e colaboram para um melhor entendimento e exploração das idiossincrasias de mediações pedagógicas em ambientes virtuais de aprendizagem. PRELIMINARY ANALYSIS OF TUTORING ACTIVITY IN SPECIALIZATION COURSES OF PUBLIC MANAGEMENT AND MUNICIPAL PUBLIC MANAGEMENT OFFERED BY UAB - UNIFESP: Perception of Tutors and Students ABSTRACT The possibility of servants training is a strategic resource, which contributes to the improvement of the Brazilian Public Administration, besides repositioning these within the public environment. The present article aims to qualify the instruction of public servants in specialization courses from the perception of tutors and students. This is a case study of the National Public Administration Training Program (PNAP) of the Open University of Brazil (UAB), considering the Lato sensu Postgraduate courses in Public Management (PM) and Municipal Public Management (MPM) offered by Osasco Campus of Universidade Federal de São Paulo, from internal reports and the use of electronic forms. The results show that the role of tutor is not yet consolidated, despite the positive evaluation of the actors involved. The perception of quality as a result of the management process highlights the importance of constantly monitoring of actions and also values the team's performance. This work opens new perspectives to study the activity of tutoring in the specialization courses, collaborating for a better understanding of the idiosyncrasies of pedagogical mediations in virtual learning environments. In parallel, this perceived quality may mean that more potential replicators of knowledge for improving public administration are being formed.